2017
DOI: 10.1186/s12905-017-0427-6
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, attitudes and perceptions regarding HIV and PMTCT amongst pregnant women in Guinea-Bissau– a qualitative study

Abstract: Background: The human immunodeficiency virus (HIV) continues to be a major cause of maternal and infant mortality and morbidity in sub-Saharan Africa. Prevention of mother-to-child transmission of HIV (PMTCT) strategies have proven effective in decreasing the number of children infected in utero, intrapartum and during the breastfeeding period. This qualitative study explores knowledge and perceptions of HIV amongst pregnant women, healthcare workers' experiences of the national PMTCT services, and barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…This is in line with findings of other study done in Ethiopia revealed that health workers are not happy to handle deliveries for women who are known HIV positive due to fear of accidental infection [22]. Other studies have also had similar findings [17,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with findings of other study done in Ethiopia revealed that health workers are not happy to handle deliveries for women who are known HIV positive due to fear of accidental infection [22]. Other studies have also had similar findings [17,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…Frequently mentioned individual and family related factors identified in this study were fear of divorce, lack of family support, lack of partner support and lack of time. Like our research, other studies found that non-disclosure of HIV status, fear of divorce, fear of HIV stigma, and lack of partners support were some of the most common barriers to PMTCT service utilization [16,[19][20][21][22][23][24][25][26]. Another study in Sudan [27], and in Malawi [28] also revealed that women are not likely to disclose their HIV status due to stigma.…”
Section: Discussionsupporting
confidence: 72%
“…The low refusal rate in this study may support the high acceptability of opt-out testing observed in other countries [ 32 36 ]. However, qualitative research from Guinea-Bissau suggests that testing around the time of delivery may in some instances have been done without adequate informed consent, which may have contributed to the high testing rates observed in this study [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main barriers to adherence were disbelief in ARV efficacy to prevent HIV transmission from mother to child, unsupportive partners, and fear of stigma and discrimination from community members [ 23 , 38 , 41 43 ]. Women’s doubts regarding ARV efficacy were commonly reported as a main challenge to adherence in PMTCT for asymptomatic participants, as documented in several studies in East Africa [ 19 , 33 , 44 ], as they do not experience a tangible benefit from treatment.…”
Section: Discussionmentioning
confidence: 99%